Side Effects and Research Progress of Immune Checkpoint Inhibitors - Li, Yichen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Immune checkpoint inhibitor (ICI) is a new type of tumor treatment drug, also known as immunotherapy drug. They target "checkpoint" molecules in the body’s immune system that prevent immune cells from attacking cancer cells. They target "checkpoint" molecules in the body’s immune system that prevent immune cells from attacking cancer cells. The use of immune checkpoint inhibitors can help control or treat certain types of cancer by promoting the restoration of inactivated immune cells and enhancing the immune system’s ability to attack. -This article focuses on skin reactions, immune pneumonitis, and adverse reactions in the thyroid and digestive tract. Through the analysis of recent relevant research, this question summarizes several different side effects, their causes and treatments. Although there are many treatments to deal with the side effects of this drug, it is important to note that the side effects of this drug are not always well understood. There are many treatments to deal with the related side effects, these side effects are still a barrier to the current use of ICIs. Future development directions should focus more on the development of ICIs. directions should focus more on the development of new targets, optimization of drug pharmacokinetics, and alleviation of side effects caused by ICIs.